Pengembangan Media Pembelajaran Canva Mata Pelajaran PAI & Bp Fase D – Sekolah Menengah Pertama - Anizak Umilatifah; Faridi Faridi (Jurnal Budi Pekerti Agama Islam, 2024)
Today's students, often referred to as the digital generation, tend to be more interested and responsive to interactive and visual learning media. However, traditional teaching methods that tend to be monotonous are often unable to fulfil students' learning needs and interests. Therefore, innovation in learning approaches is necessary. One of the innovative solutions in learning media development is the use of graphic design applications such as Canva. With its user-friendly features, Canva allows teachers to create more dynamic and interesting teaching materials, which in turn can increase students' motivation and understanding of the values taught in Islamic Religious Education and Budi Pekerti. The development method or R&D using the ADDIE model is a learning design model that provides an organised process in the construction of teaching materials that can be used in both face-to-face and online learning. The use of learning media that suits students' needs not only increases their attention to the lesson, but also provides a comprehensive learning experience, reinforces a thorough understanding of the material, and encourages students' active involvement in the learning process. Thus, students have greater opportunities to develop their creativity and potential in a supportive learning environment. Learning media plays an important role in improving student learning outcomes by providing an engaging and efficient teaching-learning process. It allows students to understand the subject matter more easily, increases learning efficiency in accordance with the learning objectives, and improves their concentration and motivation.